Pengendalian Kualitas Produk Kopi Menggunakan Metode Seven Tools Dan Failure Mode And Effect Analysis (FMEA) Di UMKM Dharma Coffee - Aldimas Dafi Saputra; Andung Jati Nugroho (Jurnal Rekayasa Proses dan Industri Terapan, 2024)
Umkm Dharma Coffee is a medium to lower business engaged in processing coffee beans into coffee powder. The problems that arise are defective products such as inappropriate weight and damaged packaging containers. From data from July to December 2022, with a total production volume of 2,760 pcs, there were 219 product defects, including 141 defective product defects and 78 damaged packaging container defects. Therefore, to reduce the number of product defects, it is necessary to support the company's management and production employees. The purpose of this research is to find out the causes of product defects using the Seven Tools method and statistically mapping the problems in order to see corrective actions that must be taken based on the factors that cause product defects using the Failure Mode And Analysis (FMEA) method. From the results of the SOD analysis, it was obtained that the highest RPN value was 36 in the damaged packaging container. The recommendations for improvement given are that companies must implement clear SOP, conduct job education and training for employees so that later they can maximize the production process in the company.